2017
DOI: 10.1186/s13052-017-0406-4
|View full text |Cite
|
Sign up to set email alerts
|

NBAS mutations cause acute liver failure: when acetaminophen is not a culprit

Abstract: BackgroundPediatric acute-liver-failure due to acetaminophen (APAP) administration at therapeutic dosage is rare, while viral infections and metabolic defects are the prevalent causes. Yet, as acetaminophen is routinely used in febrile illnesses, it may be mistakenly held responsible for the acute liver damage.Case presentationAn 11 month old boy had been on acetaminophen for 10 days (total dose 720 mg = 72 mg/kg) when he developed acute-liver-failure with encephalopathy. As he rapidly improved on N-acetylcyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Progressive reduction in NK cells numbers has been described by Garcia Segarra et al (15) and then by Ricci et al (10). As Figure 2 demonstrates, the patients who had immunodeficiency and bone disease had mutations distributed along the gene, with no particular domain predominance (10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(27)(28)(29)(30)(31)(32)(33)(34)(35), current study).…”
Section: Literature Reviewsupporting
confidence: 72%
See 1 more Smart Citation
“…Progressive reduction in NK cells numbers has been described by Garcia Segarra et al (15) and then by Ricci et al (10). As Figure 2 demonstrates, the patients who had immunodeficiency and bone disease had mutations distributed along the gene, with no particular domain predominance (10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(27)(28)(29)(30)(31)(32)(33)(34)(35), current study).…”
Section: Literature Reviewsupporting
confidence: 72%
“…mortality. Although some degree of liver disease has been associated with most NBAS variants, the mutations associated with severe liver phenotype were either loss-offunction or missense mutations predominantly located in the N-terminal and in the middle part of the NBAS gene (c.409C>T identified in 5 patients: c.680A>C;1749G>A, c.809G>C;2926del, c.1018G>C;2674G>T, c.2819A>C, and c.2819A>C) (15,18,(27)(28)(29)(30)(31).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Starting in infancy, episodes of hepatic insufficiency recur. These episodes may be preceded by fever (and thus be ascribed to antipyretics, in particular paracetamol)[1-3]. They may not be restricted to childhood[4,5] and may be fatal[6].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, as in the case of our proposita, individuals harboring the p.Arg1914His variant did not present with RALF or severe hepatic disease manifestations (Park et al, 2017). In contrast, most NBAS truncating variants reported to date have been found in patients affected with early‐onset fever‐triggered RALF (Calvo et al, 2017; Haack et al, 2015; Li et al, 2017; Regateiro et al, 2017; Sunwoo et al, 2018). The p.Arg1914His variant is located in exon 45 but its effect on the NBAS protein is unclear because it lies within the C‐terminal domain of as yet unknown function.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al, 2017 reported on a brother and sister with short stature, progeroid face, normal intelligence, and Pelger‐Hüet anomaly but also frequent upper respiratory infections, elevated serum liver enzymes levels and optic atrophy with foveal hypoplasia not previously reported. Several recent reports have emphasized the occurrence in individuals diagnosed with SOPH syndrome of: RALF (Calvo et al, 2017; Cardenas, DiPaola, Adams, Holtz, & Ahmad, 2017; Lenz et al, 2019; Ono et al, 2019; Regateiro et al, 2017; Rius et al, 2018; Staufner et al, 2015; Wang et al, 2018), ocular manifestations (Nucci et al, 2019), growth hormone deficiency (Li et al, 2018), short stature or severe skeletal involvement (Balasubramanian et al, 2017; Kim et al, 2017; Palagano et al, 2018), and early onset of recurrent or severe infections due to abnormalities in both antibody and cell‐mediated immunity documenting a combined immunodeficiency (Balasubramanian et al, 2017; Capo‐Chichi et al, 2015; Li et al, 2018; Regateiro et al, 2017; Segarra et al, 2015). These individuals required frequent antibiotic treatments, and a few were successfully treated with long‐term IgG replacement therapy (Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%